Absence of Intraocular Infections after Hematopoietic Stem Cell Transplantation at a Single Center: The Experience with Current Preventive Regimens. (April 2014) - Stoyanova, Elena I.; Riemens, Anjo; Lokhorst, Henk M.; te Boome, Liane; Rothova, Aniki
Abstract Purpose: To investigate the prevalence of intraocular infections after allogeneic stem cell transplantation (allo-SCT). Methods: The study design was a single institutional retrospective noncomparative cohort of 135 consecutive patients in 2006 and 2007 who underwent allo-SCT for hematological malignancy. The primary outcome was the development of intraocular infections after allo-SCT and secondary outcome consisted of development of other ocular disorders during follow-up. Results: The most frequent ocular sequel to allo-SCT included ocular graft-versus-host disease (GvHD), which developed in 37/135 patients (27%). Intraocular infection occurred in 1 of 135 patients (0.7%). This patient developed infectious chorioretinitis together with osteomyelitis, endocarditis, and brain abscess with fungus Scedosporium and was successfully treated with a combination of voriconazole, amphotericine B, and surgical interventions. Viral and/or bacterial intraocular infections were not observed at all. Conclusions: Intraocular infections after allo-SCT are currently uncommon due to systematic use of preemptive treatment regimens, frequent controls, and early treatment of systemic infections.